2016
DOI: 10.1002/chem.201601608
|View full text |Cite
|
Sign up to set email alerts
|

Modified Guanines as Constituents of Smart Ligands for Nucleic Acid Quadruplexes

Abstract: Repetitive guanine-rich nucleic acid sequences play a crucial role in maintaining genome stability and the cell life cycle and represent potential targets for regulatory drugs. Recently, it has been demonstrated that guanine-based ligands with a porphyrin core can be used as markers of G-quadruplex assemblies in cell tissues. Herein, model systems of guanine-based ligands are explored by DFT methods. The energies of formation of modified guanine tetrads and those of modified tetrads stacked on the top of natur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 80 publications
0
10
0
Order By: Relevance
“…Tetrads can, in addition, form a π-stacking interaction with other planes, leading to a super structure composed of the superposition of different tetrads, up to three or four units. Interestingly, the specific arrangements dictated by the Hoogsteen hydrogen bonds [37,38,39,40] lead to an accumulation of negative charge close to the center of the plan, hence G4s need to be stabilized by the inclusion of cations, such as K + and Na + , in their central channel [41]. G4s may exist in a delicate equilibrium between different conformers differing for the orientation of the dihedral angles of the backbone, giving rise to parallel, antiparallel, and hybrid arrangements [42].…”
Section: Introductionmentioning
confidence: 99%
“…Tetrads can, in addition, form a π-stacking interaction with other planes, leading to a super structure composed of the superposition of different tetrads, up to three or four units. Interestingly, the specific arrangements dictated by the Hoogsteen hydrogen bonds [37,38,39,40] lead to an accumulation of negative charge close to the center of the plan, hence G4s need to be stabilized by the inclusion of cations, such as K + and Na + , in their central channel [41]. G4s may exist in a delicate equilibrium between different conformers differing for the orientation of the dihedral angles of the backbone, giving rise to parallel, antiparallel, and hybrid arrangements [42].…”
Section: Introductionmentioning
confidence: 99%
“…Guanine quartets represent a homodromic species, and thus, addition of another guanine molecule is expected to strengthen existing hydrogen bonds. As mentioned in the Introduction, hydrogen bond cooperativity in G 4 and in its modified counterpart was recently investigated by Fonseca Guerra et al 53 and Durec et al 54 who demonstrated that it is not due to resonance-assisted hydrogen bonding, as had been previously thought, but results from charge separation within the σ electron system. Their conclusions are based on the results obtained using energy decomposition analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…47−51 Besenbacher and co-workers 52 ascribed the cooperativity of hydrogen bonds in guanine quartets to resonance-assisted hydrogen bonds, whereas Fonseca Guerra and co-workers 53 demonstrated that it is due to donor−acceptor orbital interaction in the σ-electron system accompanied with charge separation. To the best of our knowledge, the only investigation of metal ions' (or larger ligands') impact on hydrogen bond cooperativity in guanine quartets was performed by Durec et al 54 Interaction of guanine quartets and quadruplexes with alkali ions has been thoroughly theoretically investigated. 47,50,55−67 On the other hand, publications with detailed theoretical studies of guanine supramolecular structures with alkaline earth cations are scarce.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The situation has changed with the advance of modern DFT methods, which, in combination with a posteriori dispersion corrections, have been applied to large‐scale GQ fragments (consisting of hundreds atoms) and proved to provide valuable insights into structures and energetics of quadruplex stems. The pioneering DFT‐D3 study by Šponer and co‐workers, who employed two‐stack (two parallel G‐tetrads) dinucleotide models, was published in 2013 and predicted the relative stability of seven GQ stem topologies .…”
Section: Introductionmentioning
confidence: 99%
“…The situation has changed with the advance of modernD FT methods, which, in combinationw ith ap osteriori dispersion corrections, [44] have been applied [20,[45][46][47][48] to large-scale GQ fragments (consisting of hundreds atoms) andp roved to provide valuablei nsights into structures and energetics of quadruplex stems.T he pioneering DFT-D3 study by Šponer and co-workers, who employedt wo-stack (two parallelG -tetrads) dinucleotide models, was published in 2013 andp redicted the relative stabilityo fs even GQ stem topologies. [20] In contrastt op revious MD simulations, [19] DFT-D3 computations clearlyi ndicate that the parallel( P)s tructure with the AA stem orientation is more stable than the antiparallel (AP)G Qw ith the SA stem, [20] which is in line with the fact that quadruplexese xperimentally tend to form all-parallel stemsw ith all-anti orientation of nucleobases.…”
Section: Introductionmentioning
confidence: 99%